The Evaluating Land Regulation Challenges in Mitigating Gentrification: Insights from Bali's Mass Tourism Impact - Yudiantika, Kadek Agus; Prasada, Dewa Krisna (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
Gentrification is a complex socio-economic phenomenon that often occurs in tourism areas, where areas previously inhabited by lower-class residents are transformed into more prosperous neighborhoods. In Bali, significant tourism growth, with more than 5.5 million foreign tourists, has driven demand for land and property, especially from wealthy investors and foreigners. This has led to a surge in property prices that are unaffordable for locals, who on average have an income of around Rp 3.5 million per month. Drastic increases in land prices, especially in regions such as Canggu and Ubud, have resulted in the marginalization of local communities and the eviction of indigenous peoples, while also highlighting the growing gap between the rich and the poor. This study aims to explore the relationship between inadequate land regulation and the gentrification phenomenon triggered by mass tourism in Bali. Using socio-legal methods, this study analyzes primary and secondary data, including national regulations and legal literature. The results show that gaps in land regulation, such as the use of nominee agreements and lack of oversight of land ownership by foreign investors, exacerbate gentrification. Therefore, it is important to improve existing regulations by emphasizing the protection of the rights of local communities and the development of inclusive land-use policies. This study recommends the involvement of local communities in every stage of tourism development, as well as the enforcement of laws that limit foreign dominance in property ownership. As such, the principle of social justice should be the basis of tourism planning in Bali, ensuring that economic benefits are evenly distributed and supporting the cultural sustainability of local communities.